Muybridge and mobility - Cresswell, Tim; Ott, John, 1971- (Defining moments in photography, 2022)
"In 1878, Edward Muybridge successfully photographed horses in motion, proving, at the behest of railroad tycoon and former governor of California Leland Stanford, that all four hooves leave the ground for a split second during full gallop. This was an accumulation of Muybridge's decades-long investigations into instantaneous photography, amassed in his masterpiece Animal Locomotion, which combined art and science to capture movements that could not be distinguished by the human eye. Muybridge became one of the most influential photographers of his time, and his stop-motion technique, an early form of animation, helped pave the way for the motion picture industry, born a short decade later. Muybridge's famous motion studies are the subject of this sixth volume of Defining Moments in Photography. Coauthored by a cultural geographer and an art historian, this book re-examines the motion studies as historical forms of 'mobility,' in which specific forms of motion were given extraordinary significance and accrued value. For Tim Cresswell, mobility is contextualized within the transformations of movement that marked the nineteenth century through the inventions of the railroad, steamship, airplane, and telegraph lines. For John Ott, mobility represents the possibilities of social movement for African Americans, through the limited agency and social mobility of Black athletes as they moved between and amidst the spaces of Anglo-Philadelphia. Cultural geographer Cresswell sees Muybridge's pictures as interventions in knowledge and experience, while art historian Ott regards them as opportunities to investigate larger social ramifications and possibilities. Together, these complementary essays move away from traditional readings of Muybridge's works and instead offer new interpretations through a lively, interdisciplinary exchange"--